2008
DOI: 10.1002/jcp.21605
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of human embryonic stem cells into osteogenic or hematopoietic lineages: A dose‐dependent effect of osterix over‐expression

Abstract: Enhanced differentiation of human embryonic stem cells (HESCs), induced by genetic modification could potentially generate a vast number of diverse cell types. Such genetic modifications have frequently been achieved by over-expression of individual regulatory proteins. However, careful evaluation of the expression levels is critical, since this might have important implications for the differentiation potential of HESCs. To date, attempts to promote osteogenesis by means of gene transfer into HESCs using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 51 publications
(65 reference statements)
2
14
0
Order By: Relevance
“…Previous studies have reported hESC differentiation into skeletal cells [5,7,37,38] and other lineage cells [39][40][41] based on initial differentiation of hESCs as hEBs. For example, it has been reported that early mesoderm markers are expressed during hEB formation and that osteogenic cells can be induced by treating hEB with osteoblastic induction mixture [12,33,36,42].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported hESC differentiation into skeletal cells [5,7,37,38] and other lineage cells [39][40][41] based on initial differentiation of hESCs as hEBs. For example, it has been reported that early mesoderm markers are expressed during hEB formation and that osteogenic cells can be induced by treating hEB with osteoblastic induction mixture [12,33,36,42].…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown effective osteoblast generation from human ES cell cultures when treated with ascorbic acid, BGP, and Dex, as with mouse. [26][27][28] Therefore, it is envisaged that osteoblast generation may occur through similar pathways between human and mouse ES cells. In addition, the proposed surface modification culture described here could be transferred to human ES cells, and therefore, it is hoped that the findings here may result in future enhancement of osteoblast formation from human ES cells.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, through human iPS cell differentiation, genetically identical somatic cells could be generated for the treatment of a wide variety of diseases. The human iPS cells were shown to be able to differentiate into neural cells [8][9][10][11], osteogenic cells [12], cardiac cells [13], adipogenic cells [14], pancreatic cells [15,16], vascular cells [17], hematopoietic [12,18] and endothelial cells [18]. However, the directed differentiation of human iPS cells into hepatic cells has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%